STRATEGI KOMUNIKASI PEMASARAN DALAM MENINGKATKAN JUMLAH PENGUNJUNG PUSAT LATIHAN GAJAH (PLG) SEBELAT BENGKULU UTARA - Astuti, Linda; Oktridarti, Levy; Rosyadi, Imron; Tika, Yori Manis; Parwito, Parwito (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2022)
This study aims to identify the application of the marketing mix model as a marketing communication strategy for increasing the number of tourist visits to elephant training centres (PLG). This study used the descriptive-qualitative method. The survey results show that marketing communications carried out by natural tourism managers at elephant training centres (PLG) with a marketing mix, personal selling, word-of-mouth marketing (WOM), and direct marketing can increase tourist visits to the elephant training centre. The supporting factors for the marketing communication strategy are the high tourism potential and information and communication technology development. At the same time, the inhibiting factors are limited funds, damaged roads to tourist attractions, and limited internet networks.